"You Feel Like Normal Sex is not Enough Anymore"1: Women's Experiences of Coercive and Unwanted Anal Sex with Men. (September 2022) - Faustino, Maria João; Gavey, Nicola
In this article, we explore the gendered dynamics of coercion described by 18 women we interviewed about their experiences of unwanted and nonconsensual heterosexual anal sex. Several women referred to what they believed to be the normative status of heterosexual anal sex. In many cases, the socially coercive effects of perceived norms intertwined with threads of interpersonal coercion, leaving women feeling pressured to agree to, or little room to refuse, anal sex they did not want. We discuss the ways that new sexual norms can translate into new pressures for women within the gendered framework of heterosexual relationships.